The coronavirus crisis as a world-historic event in the digital era - Tsekeris, Charalambos; Zeri, Persefoni (Sociološki pregled, 2020)
The world-historic event of the COVID-19 pandemic has once more confirmed that we live in a hyperconnected world society and that, nowadays, epidemics do not count as merely natural phenomena anymore. In such context, the present paper aims to interpret the complex relationship between the society and COVID-19, with emphasis on the role played by different forces in the field of information policy and public perceptions in general. For this reason, we elaborate on cultural factors, as well as on emotions like responsibility, trust, and fear during the crisis. We also focus on the dynamics of contemporary media in relation to public images of the pandemic, drawing upon relevant findings. Overall, this casts a fresh sociological and interdisciplinary light on the current pandemic as a relational process and a digital media-driven phenomenon.
Keywords: coronavirus crisis; digital media; trust, fear; Greece